PENGARUH AKTIVITAS, LIKUIDITAS DAN SOLVABILITAS TERHADAP KEBIJAKAN DIVIDEN PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Ridwan Boli Meran, - (2019)
This study aims to determine the effect of Activity proxied with Total Assets Turnover (TATO), Liquidity proxied by Current Ratio (CR), and Solvability proxied by Debt to Equity Ratio (DER) toward Dividend Policy proxied by Dividend Payout Ratio (DPR). Population in this study are consumer goods industry companies listed in Indonesia Stock Exchange (IDX) 2014-2017. The technique of determination of the sample using the method of purposive sampling and obtained 16 consumer goods companies with a research period of four years to obtain 64 units of samples. Data analysis was done using Microsoft Excel 2007 and hypothesis testing in this research using Data Panel Regression Analysis with E-Views 9.0 program and significance level of 5%. The result of the research shows that (1) Activity (TATO) has no effect on Dividend Policy (DPR), (2) Liquidity (CR) has no effect on Dividend Policy (DPR) and (3) Solvability (DER) has no effect on Dividend Policy (DPR).